Kebijakan Kriminalisasi Terhadap Terorisme (Catatan Terhadap Uu Pemberantasan Tindak Pidana Terorisme) - K.A. Bukhori (Jurnal Ilmu Hukum, 2013)
Since the terrorist events of World Trade Centre, New York and the tragedy of Bali October 12, 2002 is the biggest act of terror that resulted in civilian casualties in the world. As a result of terror arising pro-cons who are involved in this tragedy. Despite its pro-cons who the mastermind of this bombing, here the authors raised the issue of terrorism is approached through a policy of criminalization, criminal law involves two issues, namely whether the justification for criminalizing an act as criminal, and whether the criteria used to criminalize, this becomes especially important issue of terrorism because terrorism is closer to a crime of violence related to political offenses and human rights issues.